2018
DOI: 10.4081/idr.2018.7785
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Invasive Pulmonary Aspergillosis during Treatment for Acute Exacerbation of Interstitial Lung Disease

Abstract: Prolonged immunosuppressive therapy is a risk factor for invasive pulmonary aspergillosis. We report a case of a 79-yearold man who underwent immunosuppressive therapy with methylprednisolone and cyclosporine for an acute exacerbation of interstitial lung disease. Ten days after initiation of immunosuppressive therapy, the patient reported night sweats and purulent sputum, and chest computed tomography scan revealed consolidation. He was diagnosed with invasive pulmonary aspergillosis, and required vasopressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…7 It is commonly used in clinical settings as an antifungal agent for IPA treatment in patients with impaired renal function, and recent studies have explored its use as a first-line treatment for IPA. 17,18 A prospective study involving 11 countries confirmed the efficacy and tolerability of caspofungin in highrisk populations with IPA, such as those with blood diseases or tumors. 22 Similarly, a German multicenter study determined that a daily caspofungin dose of 200 mg was safe for in vivo use.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…7 It is commonly used in clinical settings as an antifungal agent for IPA treatment in patients with impaired renal function, and recent studies have explored its use as a first-line treatment for IPA. 17,18 A prospective study involving 11 countries confirmed the efficacy and tolerability of caspofungin in highrisk populations with IPA, such as those with blood diseases or tumors. 22 Similarly, a German multicenter study determined that a daily caspofungin dose of 200 mg was safe for in vivo use.…”
Section: Discussionmentioning
confidence: 95%
“…However, microbial cultures require several days or weeks to grow, and invasive sampling for histopathological examinations is not feasible for many patients. 17,18 Our center's medical records (unpublished data) revealed an increase in the admission rates of patients with COPD and IPA. This increase in the admission rate of patients with COPD complicated by IPA necessitates further studies to better understand the factors contributing to these increases in disease prevalence and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations